On the Perceptions of Russia as an Educational Destination by the Students at German University - L. А. Savelchev (Управленческое консультирование)
Purpose. The purpose of the article was to explore how Russia is perceived as an educational destination among undergraduate (B. A.) and postgraduate (M. A.) students at Rhine-Waal University of Applied Sciences (Kleve, Germany) during the summer semester 2022.Methods. The research was conceived as a reflective study based on the case-oriented research design and with a single case examined: the Rhine-Waal University of Applied Sciences (Kleve, Germany) and its undergraduate (B. A.) and postgraduate (M. A.) students. To address the research question: “How is Russia being perceived as an educational destination by undergraduate (B.A) and postgraduate (M.A) students at Rhine-Waal University of Applied Sciences in Germany?”, a mixed method was selected with archival and document-based research which was paired with a survey as a data collection technique; and a content analysis as a strategy for data analysis.results. Results of this survey have showed that 79% of respondents would like to visit Russia, but only 18% of respondents may consider Russia as a place to go studying (results are based on 33 replies out of 7390 students in total — the justification of small sampling is explained in the Methods part). Strikingly low interest to study in Russia was explained by 1) other educational destination preferences; 2) language barrier, and 3) lack of information on the Russian study programs and 4) insufficient financial support of studying in Russia. In addition, the survey results indicated that the negative perceptions of Russia as an educational destination could be related to the different values held by the students at the Rhine-Waal University of Applied Sciences, and those held by general population in Russia (as perceived by the students), but this would require further investigation.Conclusions. There are three major findings resulting from this study. Firstly, there is an inadequate attention in International Relations’ literature on the influence of international student mobility and change in students’ worldview and values. Secondly, higher education and international student mobility are considered as one of the instruments for value promotion and factors contributing to the soft power of the states. Thirdly, the results of Rhine-Waal University of Applied Sciences case seem to confirm Sylvie Lomer’s hypothesis that students are already positively predisposed to the country where they intend to go studying.